(untitled) (International Journal of Health, Animal Science and Food Safety, 2014)
Soybean and whey are two common protein sources used in piglet feeding; however, their effects on pro-inflammatory responses remain unclear. The present study investigated the expression of various genes implicated in the activation/deactivation of porcine phagocytes post-weaning. Eighteen piglets were divided into two groups based on the main protein source of their diet; soybean (SB) or whey proteins (WP). Blood phagocytes were isolated at 72 days of age. Expression of urokinase plasminogen activator (u-PA), u-PA receptor (u-PAR), plasminogen activator inhibitors 1 and 2, intercellular adhesion molecule 1 (ICAM-1), inducible NO synthase (iNOS), cyclo-oxygenase-2 and interleukin-10 (IL-10) in activated monocytes and neutrophils (except IL-10) was determined by quantitative PCR. Expression of u-PAR, ICAM-1 and iNOS were lower in both cell types obtained from SB-fed piglets compared to WP-fed piglets. In conclusion, a SB-based diet, compared with a WP diet, is associated with reduced expression of crucial pro-inflammatory genes in porcine phagocytes.